2022
DOI: 10.1186/s43019-022-00161-3
|View full text |Cite
|
Sign up to set email alerts
|

Does the degree of intraoperatively identified cartilage loss affect the outcomes of primary total knee arthroplasty without patella resurfacing? A prospective comparative cohort study

Abstract: Purpose The aim of this study was to investigate whether the degree of patellar cartilage loss confirmed during index surgery affects the clinical and radiologic outcomes of total knee arthroplasty (TKA) performed without patellar resurfacing. Methods We prospectively divided 2012 patients with a minimum follow-up of 12 months into two groups according to intraoperatively graded cartilage lesions graded using the International Cartilage Repair S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Holland et al [10] reported that there was no difference in the Oxford Knee Score, AKP, and Kujala AKPS between patients with and without patellar cartilage loss after TKA without patellar resurfacing. Park et al [23] and Shon et al [33] found that the visual assessment of cartilage according to the ICRS grade was not significantly associated with clinical outcomes and AKP. Our results are consistent with previous research showing that postoperative AKP cannot be predicted by the degree of cartilage defects alone.…”
Section: Discussionmentioning
confidence: 99%
“…Holland et al [10] reported that there was no difference in the Oxford Knee Score, AKP, and Kujala AKPS between patients with and without patellar cartilage loss after TKA without patellar resurfacing. Park et al [23] and Shon et al [33] found that the visual assessment of cartilage according to the ICRS grade was not significantly associated with clinical outcomes and AKP. Our results are consistent with previous research showing that postoperative AKP cannot be predicted by the degree of cartilage defects alone.…”
Section: Discussionmentioning
confidence: 99%
“…Varus and valgus were designated as positive and negative HKA angles, respectively [ 16 ]. Additionally, the lateral distal femoral angle (LDFA) and medial proximal tibial angle (MPTA) were assessed to examine the preoperative phenotype and implant position in the coronal plane [ 17 , 18 ]. The LDFA was defined as the angle between the line parallel to the femoral condyle and the mechanical axis of the femur.…”
Section: Methodsmentioning
confidence: 99%
“…The HKA angle was defined as the angle subtended by a line drawn from the centre of the femoral head to that of the knee and a line drawn from the centre of the knee to that of the talus on whole‐leg standing radiographs; positive and negative HKA angles indicate varus and valgus, respectively [26]. The lateral distal femoral angle (LDFA) and medial proximal tibial angle (MPTA) were measured to investigate the preoperative phenotype and implant positioning in the coronal plane [27, 32]. The LDFA angle was defined as the lateral angle between the line parallel to the femoral condyle and mechanical axis of the femur.…”
Section: Methodsmentioning
confidence: 99%